1991
DOI: 10.1073/pnas.88.18.7938
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent channels from excised patches of Limulus ventral photoreceptors are opened by cGMP.

Abstract: The identity of the second messenger that directly activates the light-dependent conductance in invertebrate photoreceptors remains unclear; the available evidence provides some support for cGMP and Ca2'. To resolve this issue we have applied these second messengers to membrane patches excised from the light-sensitive lobe of Limulus ventral photoreceptors. Our results show that these patches contain channels that can be opened by cGMP, but not by Ca2+. These cGMP-activated channels closely resemble the channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Considering that cyclic nucleotides also function as internal messengers for chemoreception in the ciliary neurons of the olfactory epithelium, and that in those cells the cyclic nucleotide-gated channels are also blocked by diltiazem, by 3',4'-dichlorobenzamil and by amiloride (Kolesnikov, Zhainazorov & Kosolapov, 1990;Frings, Lynch & Lindemann, 1992), an extension of this proposition is that a similar cyclic nucleotides-based signalling cascade has evolved in a variety of sensory cells of ciliary origin. This, of course, does not exclude the possibility that some elements of this pathway may also be found in other cells; excitatory effects of cGMP have been reported in patches of Limulus rhabdomeric membrane (Bacigalupo, Johnson, Vergara & Lisman, 1991), and a cGMP-activated channel expressed in the eyes and antennae of Drosophila has been cloned (Baumann, Frings, Godde, Seifert & Kaupp, 1994). A functional link between these channels and the light-triggered phospholipase C cascade, however, has not been demonstrated, so that their participation in phototransduction remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that cyclic nucleotides also function as internal messengers for chemoreception in the ciliary neurons of the olfactory epithelium, and that in those cells the cyclic nucleotide-gated channels are also blocked by diltiazem, by 3',4'-dichlorobenzamil and by amiloride (Kolesnikov, Zhainazorov & Kosolapov, 1990;Frings, Lynch & Lindemann, 1992), an extension of this proposition is that a similar cyclic nucleotides-based signalling cascade has evolved in a variety of sensory cells of ciliary origin. This, of course, does not exclude the possibility that some elements of this pathway may also be found in other cells; excitatory effects of cGMP have been reported in patches of Limulus rhabdomeric membrane (Bacigalupo, Johnson, Vergara & Lisman, 1991), and a cGMP-activated channel expressed in the eyes and antennae of Drosophila has been cloned (Baumann, Frings, Godde, Seifert & Kaupp, 1994). A functional link between these channels and the light-triggered phospholipase C cascade, however, has not been demonstrated, so that their participation in phototransduction remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The second messenger reponsible for opening the lightactivated channels of invertebrate photoreceptors may be cGMP (Johnson et al, 1986;Bacigalupo et al, 1990Bacigalupo et al, , 1991. Previous work showed that light activates channels having a conductance of 40 pS.…”
Section: Introductionmentioning
confidence: 99%
“…If, as is indicated by experiments on excised patches (Bacigalupo et al, 1991), calcium does not bind directly to and open ion channels in the microvillar membrane, then the intermediate steps that couple calcium to the activation of ion channels impose a delay of only 1-3 msec. The significance of this result for visual excitation depends on when calcium is released during the light response.…”
Section: Speed Of Coupling Of Calcium Release To Depolarizationmentioning
confidence: 99%
“…However, it has not been possible so far to verify that released calcium can activate ion channels sufficiently rapidly to contribute to the generation of inward current during the light response. In excised patches of light-sensitive membrane, cyclic guanosine monophosphate (cGMP), but not calcium ions, activates ion channels (Bacigalupo et al, 1991). Calcium-activated production of cGMP has, therefore, been proposed to couple the elevation of Ca i to the activation of ion channels (Shin et al, 1993).…”
Section: Abstract: Phototransduction; Limulus Polyphemus; Photorecepmentioning
confidence: 99%